Generative Reading of Architectural Precedents and their use in the design process - Alireza Karimi; Mehrdad Javidinejad; Susan Habib (هنر اسلامی, 2023)
Referring to Precedents and studying them in the design process is a common activity performed by designers and if done correctly can help them solve design problems and lead to the formation of creative ideas. but, there is also a risk of superficial perception, which traps them in the trap of imitation. Therefore, how to read the Precedents and use them in the design process is of particular importance. The present study was conducted with the aim of drawing a framework and in order to create a model for generative reading of precedents and their use in the architectural design process. The generative capacity of reading precedents is related to disclosing viable principles in the analyzed work, and it aims to make the connection between analysis and design. To this end, it begins with a summary of the formalist critique approach as a model for reading architectural works and continues with a discussion of precedents as a source of design knowledge. Before concluding, it raises three important areas through three questions and examines them to draw its framework. Finally, as a conclusion, it proposes two approaches in utilizing precedents, during which we can study the precedents and approximate configuration with abstract diagrams and apply them to future situations in the first step, as well as develop them creatively to adapt to new situations at a later stage. And Discuss and apply the proposed framework as a way to study precedents in the design process.